A 4-Year Follow-Up Study of Attention-Deficit Hyperactivity Symptoms, Comorbidities, and Psychostimulant Use in a Brazilian Sample of Children and Adolescents with Attention-Deficit/Hyperactivity Disorder - Palma, Sonia M. M.; Natale, Ana Carolina M. P.; Calil, Helena M. (Frontiers in Psychiatry, 2015)
The aim of this study was to evaluate symptom persistence in attention-deficit/hyperactivity disorder (ADHD), the development of comorbidities, and psychostimulant usage patterns. Follow-up studies were conducted in 37 patients with ADHD and 22 healthy controls, aged 10 and 18, 4 years after their first assessment. The ADHD was rated as persistent if participants met all DSM-IV criteria for syndromic or sub-threshold persistence, or had functional impairments (functional persistence). Of the 37 ADHD patients we reevaluated, 75% had persistent symptoms, and psychiatric comorbidities with additional functional impairments and academic problems were more common than in controls. These follow-up findings show a high comorbidity associated with ADHD and support the importance of evaluation and treatment for ADHD and comorbidities throughout life.